Civilising globalisation : human rights and the global economy - Kinley, David (Lecturer in law) (Cambridge [U.K.] ; New York, N.Y. : Cambridge University Press, 2009)
David Kinley provides arguments for why the wealth created by economic globalization must serve the broad goals of social welfare and human rights and gives an agenda for how we can protect and promote human rights without sacrificing global economic growth.
Economic globalisation and universal human rights -- Trade and human rights -- Aid and human rights -- Commerce and human rights -- Civilising globalisation ahead.
Includes bibliographical references and index.
Keywords: Human rights; Human rights -- Economic aspects; International economic relations -- Social aspects; International trade -- Social aspects; Globalization -- Economic aspects; Globalization -- Social aspects; Political Science -- Political Freedom & Security -- Civil Rights; Political Science -- Political Freedom & Security -- Human Rights; Globalization -- Economic aspects; Globalization -- Social aspects; Human rights; Human rights -- Economic aspects; International economic relations -- Social aspects; International trade -- Social aspects; Donation by Raoul Wallenberg Institute, Nov 2019